The effects of ultrasonic solidification on aluminum - Đorđević Slavko 1 (Journal of Mining and Metallurgy. Section B: Metallurgy)
The effect of ultrasound on characteristics of solidified aluminum was shown. An ultrasonic head and ultrasonic system for modification was designed and applied to the crystallizing aluminum melt. The ultrasonic generator allows power of 50-500 W, amplitude of oscillations 10-100 um.m and the operating frequency of 25 kHz. Ultrasonic modification was done by ultrasound introduced from above into the melt. Microstructure photographs show decreasing of the grain size more than five times.